Relationship between Nasal Congestion and Quality of Life of Allergic Rhinitis Patients - Lutfiyani, Ida Zulfa; Sardjana, Andriana Tjitria Widi Wardani; Tjahyadewi, Shelly; Masfiyah, Masfiyah; Rahayu, Rahayu (Journal of Advanced Multidisciplinary Research, 2024)
Nasal congestion is the most common complaint complained of by allergic rhinitis sufferers. Symptoms of nasal congestion in allergic rhinitis can affect a person's quality of life, resulting in decreased work productivity, academic and social success. Based on previous research, the prevalence of allergic rhinitis is 10 to 30% of the world population, where nasal congestion is the most frequently reported symptom with a prevalence of 60%. The aim of this study was to determine the relationship between nasal congestion and the quality of life of allergic rhinitis sufferers among FK Unissula students. This research is an analytical research with a cross sectional design with sample criteria of Unissula Medical Faculty students Class of 2022 and 2021 who suffer from allergic rhinitis and meet the inclusion and exclusion criteria. The inclusion criteria in this research were students of FK Unissula Class of 2022 and 2021 and were willing to be research subjects. The exclusion criteria in this study were students with anatomical nasal abnormalities and those experiencing chronic rhinosinusitis with or without nasal polyps, deviated septum, adenoid hypertrophy, and neoplasms. There were 50 respondents from FK Unissula students who suffered from allergic rhinitis. It was found that 31 (62%) students had a blocked nose and 19 (38%) students did not experience a blocked nose. The research results showed that the majority of students experienced mild nasal congestion and the quality of life for the majority of students was good. The results of the analysis of the relationship between nasal congestion and the quality of life of allergic rhinitis sufferers using the Spearman test obtained p 0.048 with a correlation coefficient of 0.281. The results of the analysis above showed that there was a significant relationship between nasal congestion and the quality of life of allergic rhinitis sufferers.